PEDAGOGICAL PRINCIPLES OF ORGANIZING PHYSICAL EDUCATION LESSONS BASED ON A GENDER-SENSITIVE APPROACH (Scientific journal of the Fergana State University, 2026)
AbstractRelations between women and men in society are primarily determined by the characteristics of national culture and evolve in accordance with societal changes and living conditions. In our country, women and men have their own place and status in social life. The opportunities provided for women to realize their talents and abilities, alongside the improvement of gender relations, also influence the preservation of women's national identity, such as their reverence, respect, and attention toward them.